The impact of Emotion-Focused Counseling on Marital Issues of Infertile Couples: A Systematic Review - Nasim Shahrahmani; Sanaz Mollazadeh; Ali Taghipour; Malihe Mahmoudinia; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2023)
Background & aim: Infertile couples face different marital issues in their relationships. Emotion-focused counseling has been proposed as one of the approaches in the counseling process of infertile couples in several studies in Iran. Since effective counseling approaches with the greatest impact could help therapists to adopt the best counseling method. This systematic review was conducted to determine the effect of emotion-focused counseling on the marital issues of infertile couples.Methods: This systematic review was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). English and Persian databases including Pubmed, Scopus, Web of Science, Cochrane Library, Embase, Proquest, Magiran, SID, and Irandoc were searched by two independent researchers using the keywords of "infertility," "barrenness," "childlessness," "sterility," "emotion-oriented couple therapy" and "emotion-focused counselling" and their combinations using Boolean operators without time limit until Feb. 2023. Inclusion criteria were experimental studies that investigated the effect of emotion-focused counseling on the marital issues of Iranian infertile couples. The Cochrane risk of bias tool were used for assessing quality of articles.Results: Out of 88 articles, six articles with a sample size of 586 people were included in the systematic review. The findings revealed a significant increase in marital compatibility and commitment and a significant decrease in marital boredom and conflicts in the group receiving emotionally focused counseling. No significant effect was observed in marital satisfaction.                   Conclusion: Emotionally focused couple therapy is one of the effective counseling methods that can be used to improve the marital issues of infertile couples.